Topologizability and Power Boundedness of Convolutions and Toeplitz Operators on Power Series Spaces - Doğan, Nazlı (Birkhauser, 2026)
We characterize the topologizability and power boundedness of convolution and dual convolution operators on power series spaces.We determine necessary conditions for a Toeplitz operator to be m-topologizable, and power bounded on 1(n) and ∞(n), and consequently on H(C) and H(D).
Keywords: Toeplitz Operator; Power Series Space; Topologizable Operator; Power Bounded Operator